Етнографічні групи лемків, бойків та гуцулів у сучасній історіографії - Мусієнко, Ірина Володимирівна (Харківський національний університет ім. В. Н. Каразіна, 2011)
Стаття присвячена розгляду в сучасній історіографії проблем історії етнографічних груп українців - бойків, лемків, гуцулів. Проаналізовано доробок окремих дослідників та етапи розвитку наукових студій. Вказано, що не зважаючи на існуючу наукову літературу, що обгрунтовано визначає статус вказаних етнографічних груп як складову українців, продовжують існувати міфи про окремий русинський етнос. Отже політичне русинство - проект організації сепаратистського руху.

The article considers the problems of the history of ethnographical groups of Ukrainians - Boykos, Lemkos and Hutsuls in a modern historiography. Analyzed the scientific contribution of some scholars and development stages of research. It was pointed out that despite the existing scientific literature that reasonably defines the status of these ethnographic groups as a component of Ukrainians, myths about separate rusyn ethnos exist. Thus political rusynism is a project of the organization of separatist movement.
Ethnographical groups of the Lemkos, Boykos and Hutsuls in a modern historiography
Keywords: Boykos; ethnographical group; historiography; political rusynism; Ruthenians; Lemkos; Hutsuls; бойки; гуцули; етнографічна група; історіографія; лемки; політичне русинство; русини